The main stakes of the CNES's safety policy for space operations. Issue 2 (June 2021) - Chemoul, Bernard; Aniakou, Dr Ursula; Boloh, Loïc; Francillout, Laurent
Abstract: CNES, the French space agency, is involved in the development and exploitation of orbital systems, launch systems, balloons and launch range in French Guyana (CSG). Safety is a CNES strong value which is shared among its staff and which is embedded in all its initiatives and its own space operations. Moreover, CNES is entitled by the French government to control the correct application of the French Space Operations Act which the main objective is to ensure the protection of people, assets and environment against risks resulting from space operations. In order to fulfill the safety objectives, rules have been issued which are the core of the technical regulation order and the order regulating the operations at CSG facilities. This paper shortly describes the main principles which govern applied safety rules for authorizing the current launch, satellite and balloon operations. The development of space business in France and in Europe leads to consider new innovative projects or missions which rise new safety challenges that are listed in this paper. The stakes are to issue adapted safety regulations for managing the operations of the devised concept, but keeping the same level of safety for the protection of people on ground or in airplane, of assets and of environment as the one reached for the current space operations. In the meantime, the safety measure will be refined in order to foster the development of Space business, especially at the CSG. These questions will feed a work for updating. the French Space Operations acts and the subsequent documentation in the near future.